Analisis Manajemen Sumber Daya Aparatur di Sekretariat Kabupaten Jeneponto - Aan Saddan Husain; Juanda Nawawi; Rabina Yunus (GOVERNMENT : Jurnal Ilmu Pemerintahan, 2011)
Abstract: This study aims to understand the extent of the analysis resources of management officials (planning supervision, organizing) in increasing the civil servants and affecting factors implementation in the office of a regent jeneponto. Type research is descriptive to technique data collection observation and division kuisioner. While withdrawal sample techniques used is purposive sample it is taking a sample subjective considered representative. The research shows how important role function planning, supervision, and organizing. In the management of the an organization.Planning application of function, pengawsan, and organizing. Optimalizing efforts to through indicators as following: 1) the motivation; 2) discipline work; 3) responsibility; 4) earnestness; and 5) sincerity. Then from the implementation of the planning function, supervision and organizing, there are several factors affecting the implementation of the it is the system and procedures work, facilities and infrastructure, communication, and budget. Keywords: management, officials, servants Abstrak: Penelitian ini bertujuan untuk mengetahui sejauh mana pelaksanaan Analisis manajemen sumber daya aparatur (Perencanaan Pengawasan, Pengorganisasian) dalam peningkatan kinerja Pegawai Negeri Sipil serta faktor-faktor yang mempengaruhi pelaksanaan di Kantor Bupati Jeneponto. Tipe penelitian bersifat deskriptif dengan teknik pengumpulan data observasi dan pembagian kuisioner. Sedangkan teknik penarikan sampel yang digunakan adalah purposive sample yaitu mengambil sampel secara subjektif yang dianggap representatif. Dari hasil penelitian menunjukkan bagaimana peran penting fungsi perencanaan, pengawasan, dan pengorganisasian. dalam manajemen terhadap mekanisme suatu organisasi. Penerapan fungsi perencanaan, pengawsan, dan pengorganisasian. dapat dioptimalkan melalui indikator sebagai berikut: 1) Pemberian motivasi; 2) Disiplin Kerja; 3) Tanggungjawab; 4) Kesungguhan; dan 5) Keikhlasan. Kemudian dari proses pelaksanaan fungsi perencanaan, pengawasan dan pengorganisasian tersebut terdapat beberapa faktor yang mempengaruhi pelaksanaan, yaitu sistem dan prosedur kerja, sarana dan prasarana, komunikasi, dan anggaran.Kata kunci: manajemen, aparatur, kinerja